Antidepressant Prophylaxis Reduces Depression Risk but Does Not Improve Sustained Virological Response in Hepatitis C Patients Receiving Interferon Without Depression at Baseline: A Systematic Review and Meta-Analysis. (2013) - Al-Omari, Awad; Cowan, Juthaporn; Turner, Lucy; Cooper, Curtis
Abstract : BACKGROUND: Depression complicates interferon-based hepatitis C virus (HCV) antiviral therapy in 10% to 40% of cases, and diminishes patient well-being and ability to complete a full course of therapy. As a consequence, the likelihood of achieving a sustained virological response (SVR [ie, permanent viral eradication]) is reduced. OBJECTIVE: To systematically review the evidence of whether preemptive antidepressant prophylaxis started before HCV antiviral initiation is beneficial. METHODS: Inclusion was restricted to randomized controlled trials in which prophylactic antidepressant therapy was started at least two weeks before the initiation of HCV antiviral treatment. Studies pertaining to patients with active or recent depressive symptoms before commencing HCV antiviral therapy were excluded. English language articles from 1946 to July 2012 were included. The MEDLINE, Embase and Cochrane Central databases were searched. Where possible, meta-analyses were conducted evaluating the effect of antidepressant prophylaxis on SVR and major depression as well as on Montgomery-Asberg Depression Rating Scale and Beck Depression Index scores at four, 12 and 24 weeks. The Cochrane Collaboration tool was used to assess bias risk. RESULTS: Six randomized clinical trials involving 522 patients met the inclusion criteria. Although the frequency of on-treatment clinical depression was decreased with antidepressant prophylaxis (risk ratio 0.60 [95% CI 0.38 to 0.93]; P=0.02; I 2 =24%), no benefit to SVR was identified (risk ratio 1.08 [95% CI 0.74 to 1.57]; P=0.69; I 2 =58%). CONCLUSION: This practice is not justified to improve SVR in populations free of active depressive symptoms leading up to HCV antiviral therapy.